Ableism in mental healthcare settings: A qualitative study among U.S. adults with disabilities - Katie Wang; Joan M. Ostrove; Robert B. Manning, III; Sarah Fodero; Samuel L. Ash; Jessica Whang; Kathleen R. Bogart; Rebecca Cipollina; Michelle R. Nario-Redmond; Jonathan M. Adler; Sarah R. Lowe (Elsevier, 2024)
People with disabilities (PWD) face elevated mental health concerns and are more likely to utilize mental health services compared to their nondisabled counterparts, yet they also report higher unmet mental health service needs due to myriad attitudinal and environmental barriers to accessing care. Despite these well-documented disparities, little research has examined the nuanced lived experiences of PWD who receive mental health services. Drawing upon semi-structured interviews with 20 U.S. adults with disabilities who were diverse in race/ethnicity, sexual orientation, and gender identity, the present research examined the various structural and interpersonal processes through which ableism undermines the perceived effectiveness and relevance of mental health services. Reflexive thematic analysis identified six themes that characterized participants' ableism experiences in mental healthcare settings, including misplaced assumptions about the impact of disability on mental health, medical trauma and gaslighting, interpersonal ableism, lack of disability knowledge, accessibility challenges, and systematic ableism. These findings highlight the importance of centering PWD's voices in disability-affirmative mental health research and underscore important clinical considerations for fostering accessible and inclusive mental health services.